Worldviews and Intergenerational Altruism: Empirical Evidence for Germany - K. Ali Akkemik; Marcus Dittrich; Koray Göksal; Kristina Leipold; Masao Ogaki (European Regional Science Association (ERSA), 2013)
This paper studies the effects of differences in worldviews on parents? attitudes towards their children. We use unique German survey data containing questions on worldviews, religion, parental behavior, and socioeconomic variables. Our empirical evidence suggests that people with stronger confidence in strong disbelief in afterlife are more likely to have a tough love attitude towards their children. On the other hand, people who have strong disbelief in afterlife are less likely to have tough love attitude towards their children. Our results also indicate that people who belong to the Protestant and Catholic churches in Germany are less likely to have spoiling love attitude. On the other hand, people who have strong disbelief in afterlife are less likely to have tough love attitude towards their children.
Keywords: Z10; Z12; D64; 330; Intergenerational altruism; worldview; religion; tough love; spoiling love